If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ((5x + 10) + 1) = 4x Reorder the terms: ((10 + 5x) + 1) = 4x Remove parenthesis around (10 + 5x) (10 + 5x + 1) = 4x Reorder the terms: (10 + 1 + 5x) = 4x Combine like terms: 10 + 1 = 11 (11 + 5x) = 4x Remove parenthesis around (11 + 5x) 11 + 5x = 4x Solving 11 + 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 11 + 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x 11 + 1x = 4x + -4x Combine like terms: 4x + -4x = 0 11 + 1x = 0 Add '-11' to each side of the equation. 11 + -11 + 1x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 0 + -11 1x = 0 + -11 Combine like terms: 0 + -11 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| 4c-7=37 | | -25-11x=-6x | | -12=9+-7x | | -4(n+3)+3=-3n-3(3-n) | | 9+(3b+8)=(3b+8+9) | | 216x^4-600x^2=0 | | 3x+5x-2=4x-10 | | 2x+3=-11+4x | | 5d+3d+2d-4d=12 | | x^2+26+160=0 | | 4*-9-70=12*-9+2 | | -2+7x=5(-6+7) | | -3(7v+5)+7v=-5+3(v+8) | | 12r+17r=105 | | 2x+2x+3x-2+3x-2=3x-1+3x+3x+1 | | 9-2y=-11+6 | | -6=2n-3n | | 30y^3+28y^2-16y=0 | | 5y+9+119=180 | | 5(3)+2y=10 | | -17=-4x+3 | | 11-7(12k+2)=-(3-4k)-3k | | 2g+3(-7+2g)=1-9 | | .50x+.35(70)=44.5 | | 125+13x=21 | | -2y+6=y^2-9 | | 5(2)+2=10 | | -(3x+3)-2(3y+3)= | | 7a^3+22a^2+3a=0 | | 7(5x-2)=7(4x+6) | | x(9)=54 | | -x-2=12x |